Mengatasi Perundungan di SMKN 3 Pujut: Pendekatan Edukatif Untuk Meningkatkan Kesadaran Dan Mencegah Perundungan - Kurnia, Agus; Nuraisyah, Nuraisyah (Universitas Mataram, 2024)
Bullying is aggressive behavior that is carried out repeatedly and deliberately by one or more people towards another person who is weaker or helpless. Bullying can have a negative impact on victims, perpetrators, and witnesses of bullying, both physically, psychologically, socially, and academically. Therefore, bullying needs to be prevented and tackled in an effective and appropriate way. The purpose of this service is to overcome bullying at SMKN 3 Pujut by using an educational approach. The method used in this service is to use a peer education approach with several stages, namely observation, socialization, and evaluation. The results of this service show that an educational approach can increase awareness and prevent bullying at SMKN 3 Pujut. From the activities carried out, it can be seen that the students have become more aware of bullying and are more concerned about preventing and handling bullying. The results of the data analysis showed that there was an increase in the average score of understanding discrimination and bullying after socialization. This increase shows that socialization is effective in increasing students' understanding of discrimination and bullying. Keywords: Mental Health; Discrimination; Bullying; Students; Education